Regulating for Telecommunications Competition in Developing Countries: the case of Papua New Guinea - Bronwyn E. Howell; Petrus H. Potgieter; Ronald Sofe (International Telecommunications Society (ITS), 2018)
Papua New Guinea is a low-middle income developing Asia-Pacific island country with a relatively long history of telecommunications market development under firstly Australian administration, and latterly under a pro-competitive set of regulatory arrangements strongly influenced by Australian policy-making. Nevertheless, it demonstrates some of the weakest sector performance statistics of a range of comparable low-middle income countries in its region. Why does a country with a regulatory regime drawing on current international recommended "best practice" perform so poorly? To address this question, we develop an inquiry framework (checklist) for assessing the effectiveness of regulatory arrangements in a developing, as opposed to developed country. Whilst the framework is based on guidelines from the World Bank and the International Telecommunications Union (Blackman & Srivastava, 2011), we adapt these to take account of specific challenges arising in developing countries: limited capacity, limited commitment, limited accountability, limited fiscal efficiency and trade-offs between factors that take account of these limits (Laffont, 2005; Estache & Wren-Lewis, 2010). Applying the inquiry framework to Papua New Guinea, we find that, the most likely explanation for poor performance derives from the government being both regulator and owner of the incumbent, Telikom. Lack of investment and an unstable set of ownership arrangements have constrained Telikom from being an effective competitor. Weaknesses exist in the monitoring and enforcement of regulator accountability provisions, but are unlikely to have altered sector outcomes, although they may have contributed to obscuring poor performance. Introduction of at least one more foreign operator will be beneficial, but only if the government can clearly separate its ownership and regulatory activities and political agents can credibly commit to refraining from interfering in the operational activities of both the incumbent firm and regulatory agencies.
Keywords: 330